Assessment of laser ablation and solution-based ICP-MS applications commonly used in otolith geochemical analysis of marine teleosts - Michelle Zapp Sluis; Daniel L. Lippi; Phillip J. Sanchez; Phillip J. Sanchez; Nathaniel R. Miller; Shane A. Stephens; Beatrice P. Ferreira; Jay R. Rooker (Frontiers in Marine Science)
Different applications of inductively coupled plasma mass spectrometry (ICP-MS) have the potential to influence results of otolith geochemical assays. Laser ablation and solution-based ICP-MS were compared on paired otoliths from three species of juvenile fish representative of estuarine (red drum [Sciaenops ocellatus]), coastal/reef (gray parrotfish [Sparisoma axillare]), and pelagic (blackfin tuna [Thunnus atlanticus]) ecosystems. Additionally, two laser ablation techniques (continuous line transects and series of spots) were performed to determine whether these two commonly used approaches yielded comparable results. No significant differences existed between line transects and spots for any of the three species investigated, with high correlations occurring for all otolith element:Ca (E:Ca) values retained for statistical testing (Mg:Ca, Mn:Ca, Sr:Ca, Ba:Ca), suggesting that both laser ablation techniques produced equivalent otolith E:Ca values. In contrast, pronounced differences in E:Ca values were detected between laser ablation (across otolith transverse section) and solution-based (whole otolith dilution) applications on paired sagittal otoliths. While some E:Ca discrepancies varied among the three species, overall otolith E:Ca values were higher when quantified by laser ablation, except for Ba:Ca which tended to be higher when analyzed by solution-based ICP-MS. Differences observed between laser ablation and solution-based applications are the result of the allometric growth of the otolith and may become more pronounced in older, larger individuals as the differential growth along the otolith axes becomes less uniform with age. Further, laser ablation techniques can examine life history profiles and discern fluctuations over time, proving a preferred application over solution-based analysis.